Mathematical Communication Skills in Terms of Self Efficacy Through Guided Discovery Learning Assisted Immediate Feedback - Zulfa, Aulia; Kartono, Kartono; Nur Cahyono, Adi (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study to find patterns of mathematical communication skills in terms of self efficacy of guided discovery learning design assisted immediate feedback. The research method used is mixed method while the design is sequential explanatory. The research subjects consisted of thirty-two students of class VIIF SMP Negeri 1 Mijen, Demak. The techniques of collecting data were mathematical communication skills test and self-efficacy questionnaire. The results of this study are mathematical communication skills of students through guided discovery learning assisted immediate feedback effective, described mathematical communication skills in terms of self efficacy were categorized high, medium and low level of guided discovery learning design assisted immediate feedback.